Ablation of CD8?(+) dendritic cell mediated cross-presentation does not impact atherosclerosis in hyperlipidemic mice - Legein, Bart; Janssen, Edith M.; Theelen, Thomas L.; Gijbels, Marion J.; Walraven, Joep; Klarquist, Jared S.; Hennies, Cassandra M.; Wouters, Kristiaan; Seijkens, Tom T. P.; Wijnands, Erwin; Sluimer, Judith C.; Lutgens, Esther; et al. (Scientific Reports, 2015)
Clinical complications of atherosclerosis are almost exclusively linked to destabilization of the atherosclerotic plaque. Batf3-dependent dendritic cells specialize in cross-presentation of necrotic tissue-derived epitopes to directly activate cytolytic CD8 Tcells. The mature plaque (necrotic, containing dendritic cells and CD8 Tcells) could offer the ideal environment for cross-presentation, resulting in cytotoxic immunity and plaque destabilization. Ldlr(-/-) mice were transplanted with batf3(-/-) or wt bone marrow and put on a western type diet. Hematopoietic batf3 deficiency sharply decreased CD8?(+) DC numbers in spleen and lymph nodes (>80%; P < 0,001). Concordantly, batf3(-/-) chimeras had a 75% reduction in OT-I cross-priming capacity in vivo. Batf3(-/-) chimeric mice did not show lower Tcell or other leukocyte subset numbers. Despite dampened cross-presentation capacity, batf3(-/-) chimeras had equal atherosclerosis burden in aortic arch and root. Likewise, batf3(-/-) chimeras and wt mice revealed no differences in parameters of plaque stability: plaque Tcell infiltration, cell death, collagen composition, and macrophage and vascular smooth muscle cell content were unchanged. These results show that CD8?(+) DC loss in hyperlipidemic mice profoundly reduces cross-priming ability, nevertheless it does not influence lesion development. Taken together, we clearly demonstrate that CD8?(+) DC-mediated cross-presentation does not significantly contribute to atherosclerotic plaque formation and stability.
EVALuna2:1982

Application of machine learning algorithms for multiparametric MRI-based evaluation of murine colitis - Ellmann, Stephan; Langer, Victoria; Britzen-Laurent, Nathalie; Hildner, Kai; Huber, Carina; Tripal, Philipp; Seyler, Lisa; Waldner, Maximilian; Uder, Michael; Stürzl, Michael; Bäuerle, Tobias (PLoS ONE, 2018)
Magnetic resonance imaging (MRI) allows non-invasive evaluation of inflammatory bowel disease (IBD) by assessing pathologically altered gut. Besides morphological changes, relaxation times and diffusion capacity of involved bowel segments can be obtained by MRI. The aim of this study was to assess the use of multiparametric MRI in the diagnosis of experimentally induced colitis in mice, and evaluate the diagnostic benefit of parameter combinations using machine learning. This study relied on colitis induction by Dextran Sodium Sulfate (DSS) and investigated the colon of mice in vivo as well as ex vivo. Receiver Operating Characteristics were used to calculate sensitivity, specificity, positive- and negative-predictive values (PPV and NPV) of these single values in detecting DSS-treatment as a reference condition. A Model Averaged Neural Network (avNNet) was trained on the multiparametric combination of the measured values, and its predictive capacity was compared to those of the single parameters using exact binomial tests. Within the in vivo subgroup (n = 19), the avNNet featured a sensitivity of 91.3% (95% CI: 86.6-96.0%), specificity of 92.3% (95% CI: 85.1-99.6%), PPV of 96.9% (94.0-99.9%) and NPV of 80.0% (95% CI: 69.9-90.1%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.003) and performing significantly worse compared to none of the single values. Within the ex vivo subgroup (n = 30), the avNNet featured a sensitivity of 87.4% (95% CI: 82.6-92.2%), specificity of 82.9% (95% CI: 76.1-89.7%), PPV of 88.9% (84.3-93.5%) and NPV of 80.8% (95% CI: 73.8-87.9%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.015), exceeded by none of the single parameters. In experimental mouse colitis, multiparametric MRI and the combination of several single measured values to an avNNet can significantly increase diagnostic accuracy compared to the single parameters alone. This pilot study will provide new avenues for the development of an MR-derived colitis score for optimized diagnosis and surveillance of inflammatory bowel disease.
EVALuna2:35135

Batf3 deficiency proves the pivotal role of CD8?(+) dendritic cells in protection induced by vaccination with attenuated Plasmodium sporozoites - Montagna, G. N.; Biswas, A.; Hildner, Kai; Matuschewski, K.; Dunay, I. R. (Parasite Immunology, 2015)
Increasing evidence indicates that hepatic CD8?(+) dendritic cells (DCs) are important antigen cross-presenting cells (APC) involved in the priming of protective CD8(+) T cell responses induced by live-attenuated Plasmodium sporozoites. Experimental proof for a critical role of CD8?(+) DCs in protective pre-erythrocytic malaria immunizations has pivotal implications for vaccine development, including improved vectored subunit vaccines. Employing Batf3(-/-) mice, which lack functional CD8?(+) DCs, we demonstrate that deficiency of these particular APCs completely abolishes protection and corresponding signatures of vaccine-induced immunity. We show that in wild-type, but not in Batf3(-/-) , mice CD8?(+) DCs accumulate in the liver after immunization with live irradiation-attenuated P. berghei sporozoites. IFN-? production by Plasmodium antigen-specific CD8(+) T cells is dependent on functional Batf3. In addition, our results demonstrate that the dysfunctional cDC-CD8+ T cell axis correlates with MHC class II upregulation on splenic CD8?(-) DCs. Collectively, these findings underscore the essential role of CD8?(+) DCs in robust protection induced by experimental live-attenuated malaria vaccines. This article is protected by copyright. All rights reserved.
EVALuna:32558

BATF-dependent IL-7RhiGM-CSF+ T cells control intestinal graft-versus-host disease - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Büttner-Herold, Maike; Buchele, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (Journal of Clinical Investigation, 2018)
Acute graft-versus-host disease (GVHD) represents a severe, T cell-driven inflammatory complication following allogeneic hematopoietic cell transplantation (allo-HCT). GVHD often affects the intestine and is associated with a poor prognosis. Although frequently detectable, proinflammatory mechanisms exerted by intestinal tissue-infiltrating Th cell subsets remain to be fully elucidated. Here, we show that the Th17-defining transcription factor basic leucine zipper transcription factor ATF-like (BATF) was strongly regulated across human and mouse intestinal GVHD tissues. Studies in complete MHC-mismatched and minor histocompatibility-mismatched (miHA-mismatched) GVHD models revealed that BATF-expressing T cells were functionally indispensable for intestinal GVHD manifestation. Mechanistically, BATF controlled the formation of colon-infiltrating, IL-7 receptor-positive (IL-7R+), granulocyte-macrophage colony-stimulating factor-positive (GM-CSF+), donor T effector memory (Tem) cells. This T cell subset was sufficient to promote intestinal GVHD, while its occurrence was largely dependent on T cell-intrinsic BATF expression, required IL-7-IL-7R interaction, and was enhanced by GM-CSF. Thus, this study identifies BATF-dependent pathogenic GM-CSF+ effector T cells as critical promoters of intestinal inflammation in GVHD and hence putatively provides mechanistic insight into inflammatory processes previously assumed to be selectively Th17 drive
EVALuna2:25783

Batf-dependent Th17 cells critically regulate IL-23 driven colitis-associated colon cancer - Punkenburg, Elise; Vogler, Tina; Büttner, Maike; Amann, Kerstin Ute; Waldner, Maximilian; Atreya, Raja; Abendroth, Benjamin; Mudter, Jonas; Merkel, Susanne; Gallmeier, Eike; Rose-John, Stefan; Neurath, Markus; et al. (Gut, 2016)
IBDs have an increased risk for development of colorectal cancer (CRC). Here, we aimed at the characterisation of the functional role of Th17-associated transcription factors in sporadic and colitis-associated colon cancer in vivo.We used mice deficient or transgenic for the activating protein 1 family member basic leucine zipper transcription factor ATF-like (Batf) to evaluate the role of Th17 cells during sporadic and inflammation-induced colon carcinogenesis. We also studied the expression of Batf and ROR?t in patients with IBD and CRC.Batf but not retinoic acid-related orphan receptor ?t(ROR?t) expression was significantly increased together with interleukin (IL) 23 expression in UC but not in Crohn's disease (CD) tissue samples. In CRC also Batf but not ROR?t expression was increased and its expression correlated with the IL-23 and IL-23 receptor (IL-23R) expression. Finally, Batf but not ROR?t was coexpressed with IL-17a, IL-23R and IL-6 within CRC-infiltrating CD4(+) T cells. Functional studies in mice revealed that Batf-dependent T cells are crucial regulators of sporadic and inflammation-induced CRC. Colitis-associated Batf(-/-) tumours lacked IL-17a(+)IL-23R(+)IL-6(+)CD4(+) T cells, hence displaying characteristics reminiscent of human CRC-infiltrating CD4(+) T cells. Strikingly, Batf(-/-) tumours contained low IL-23 but high IL-17a expression levels. Tumour formation and intratumoral IL-23 expression could be restored by administration of Hyper-IL-6 consisting of IL-6 and soluble IL-6 receptor.Batf-dependent IL-23R(+)IL-6(+)CD4(+) Th17 cells critically control IL-23 driven colitis-associated tumour formation and the progression of sporadic colon tumours. Batf-dependent IL-23R(+) T cells represent a potential future therapeutic target limiting CRC progression.
EVALuna2:2026

Confocal laser endomicroscopy for diagnosing lung cancer in vivo - Fuchs, Florian; Zirlik, Sabine; Hildner, Kai; Schubert, Juergen; Vieth, Michael; Neurath, Markus (European Respiratory Journal, 2013)
Confocal laser endomicroscopy is a novel endoscopic technique that may allow imaging of living cells in lung tissue in vivo. We assessed the potential of this technique for the detection of histology during screening bronchoscopy for lung cancer. 32 patients with suspected malignancies underwent bronchoscopy with endomicroscopy using acriflavine hydrochloride. Standardised areas and localised lesions were analysed by in vivo confocal imaging during bronchoscopy and biopsies were taken. Confocal images were graded and correlated prospectively with conventional histology from biopsies. Acriflavine hydrochloride yielded high-quality confocal images and strongly labelled airway epithelial cells. No side-effects were noted. 75 522 confocal images from 56 different locations were compared prospectively with histological data from biopsy specimens. Endomicroscopy allowed subsurface imaging with detailed analysis of cellular and subcellular structures. Neoplastic changes could be predicted with high accuracy (sensitivity 96.0%, specificity 87.1%, accuracy 91.0%). Confocal laser endomicroscopy with acriflavine is a novel diagnostic tool for the analysis of living cells during bronchoscopy and permits virtual histology of neoplastic changes in the airways with high accuracy. This technique may enable the rapid diagnosis of neoplasia during ongoing endoscopy in patients with suspected lung cancer. Copyright©ERS 2013.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Bronchoscopy; Endomicroscopy; In vivo imaging; Lung cancer

Confocal Laser Endomicroscopy for Diagnosing Malignant Pleural Effusions - Zirlik, Sabine; Hildner, Kai; Rieker, Ralf; Neurath, Markus; Fuchs, Florian; Vieth, Michael (Medical Science Monitor, 2018)
BACKGROUND Confocal laser endomicroscopy (CLE) enables "in vivo" microscopic tissue diagnosis based on tissue reflectance or tissue fluorescence upon application of fluorescence agents. The aim of the present study was to evaluate CLE as a new diagnostic approach for differentiation between malignant versus non-malignant pleural effusions. MATERIAL AND METHODS In 100 patients with pleural effusions, thoracentesis was performed. Cresyl violet and acriflavine were used as contrast agents for probe-based CLE of effusions. CLE video sequences were assessed by 4 independent investigators (2 experienced in this technique, 2 with only basic knowledge). In addition, all CLE samples were evaluated by an expert pathologist (p). Results were compared with conventional cytology of effusions and histology of cell blocks. RESULTS CLE reliably permitted identification of malignant cells in pleural effusions. Sensitivity for detection of malignant effusions was 87% (p: 87%) and 81% (p: 72%) for acriflavine and cresyl violet, respectively. With regard to specificity, acriflavine and cresyl violet yielded a mean value of 99% (p: 100%) and 92% (p: 100%). CONCLUSIONS In this pilot study, CLE permitted simple and rapid detection of malignant pleural effusions. Larger prospective studies are warranted to corroborate our findings.
EVALuna2:35147

Deciphering the role of HLA-DO in immune responses after allogeneic stem cell transplantation - Zeun, Julia; Flamann, Cindy; Neubeck, S.; Bausenwein, J.; Seyler, L.; Vogler, T.; Brey, Stefanie; Büttner-Herold, Maike; Hildner, Kai; Winkler, Thomas; Bruns, Heiko; Kretschmann, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Detection of circulating extracelluar mRNAs by modified small-RNA-sequencing analysis - Akat, Kemal M.; Lee, Youngmin A.; Hurley, Arlene; Morozov, Pavel; Max, Klaas E. A.; Brown, Miguel; Bogardus, Kimberly; Sopeyin, Anuoluwapo; Hildner, Kai; Diacovo, Thomas G.; Neurath, Markus; Borggrefe, Martin; et al. (JCI Insight, 2019)
Extracellular mRNAs (ex-mRNAs) potentially supersede extracellular miRNAs (ex-miRNAs) and other RNA classes as biomarkers. We performed conventional small-RNA-sequencing (sRNA-seq) and sRNA-seq with T4 polynucleotide kinase (PNK) end treatment of total extracellular RNAs (exRNAs) isolated from serum and platelet-poor EDTA, acid citrate dextrose (ACD), and heparin plasma to study the effect on ex-mRNA capture. Compared with conventional sRNA-seq, PNK treatment increased the detection of informative ex-mRNAs reads up to 50-fold. The exRNA pool was dominated by RNA originating from hematopoietic cells and platelets, with additional contribution from the liver. About 60% of the 15- to 42-nt reads originated from the coding sequences, in a pattern reminiscent of ribosome profiling. Blood sample type had a considerable influence on the exRNA profile. On average approximately 350-1100 distinct ex-mRNA transcripts were detected depending on plasma type. In serum, additional transcripts from neutrophils and hematopoietic cells increased this number to near 2300. EDTA and ACD plasma showed a destabilizing effect on ex-mRNA and noncoding RNA ribonucleoprotein complexes compared with other plasma types. In a proof-of-concept study, we investigated differences between the exRNA profiles of patients with acute coronary syndrome and healthy controls. The improved tissue resolution of ex-mRNAs after PNK treatment enabled us to detect a neutrophil signature in ACS that escaped detection by ex-miRNA analysis.
CRIS-Team WoS Importer:2019-05-17

Dynamic imaging of iel-iec co-cultures allows for quantification of cd103-dependent t cell migration - Enderle, Karin; Dinkel, Martin; Spath, Eva-Maria; Schmid, Benjamin; Zundler, Sebastian; Tripal, Philipp; Neurath, Markus; Hildner, Kai; Neufert, Clemens (International Journal of Molecular Sciences, 2021)
Intraepithelial lymphocytes (IEL) are widely distributed within the small intestinal epithelial cell (IEC) layer and represent one of the largest T cell pools of the body. While implicated in the pathogenesis of intestinal inflammation, detailed insight especially into the cellular cross-talk between IELs and IECs is largely missing in part due to lacking methodologies to monitor this interaction. To overcome this shortcoming, we employed and validated a murine IEL-IEC (organoids) ex vivo co-culture model system. Using livecell imaging we established a protocol to visualize and quantify the spatio-temporal migratory behavior of IELs within organoids over time. Applying this methodology, we found that IELs lacking CD103 (i.e., integrin alpha E, ITGAE) surface expression usually functioning as a retention receptor for IELs through binding to E-cadherin (CD324) expressing IECs displayed aberrant mobility and migration patterns. Specifically, CD103 deficiency affected the ability of IELs to migrate and reduced their speed during crawling within organoids. In summary, we report a new technology to monitor and quantitatively assess especially migratory characteristics of IELs communicating with IEC ex vivo. This approach is hence readily applicable to study the effects of targeted therapeutic interventions on IEL-IEC cross-talk.
CRIS-Team Scopus Importer:2021-05-21
Keywords: CD103; Intestinal organoids; Intraepithelial lymphocytes; Life cell imaging; Lympho-cyte migration

Engineering Therapeutic Regulatory T Cells to Overexpress G Protein-Coupled Receptor 15 Improves Functional Fitness for In Vivo Gut Homing - Müller, Tanja; Liu, Lijuan; Wiesinger, Manuel; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; Diefenbach, Andreas; et al. (Gastroenterology, 2025)
CRIS-Team Scopus Importer:2025-01-31

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Expansion of IL-23 receptor bearing TNFR2+ T cells is associated with molecular resistance to anti-TNF therapy in Crohn's disease - Schmitt, Heike; Billmeier, Ulrike; Dieterich, Walburga; Rath, Timo; Sonnewald, Sophia; Reid, Stephen; Hirschmann, Simon; Hildner, Kai; Waldner, Maximilian; Mudter, Jonas; Hartmann, Arndt; Grützmann, Robert; et al. (Gut, 2018)
OBJECTIVE: Anti-tumour necrosis factor (TNF) antibodies are successfully used for treatment of Crohn's disease. Nevertheless, approximately 40% of patients display failure to anti-TNF therapy. Here, we characterised molecular mechanisms that are associated with endoscopic resistance to anti-TNF therapy. DESIGN: Mucosal and blood cells were isolated from patients with Crohn's disease prior and during anti-TNF therapy. Cytokine profiles, cell surface markers, signalling proteins and cell apoptosis were assessed by microarray, immunohistochemistry, qPCR, ELISA, whole organ cultures and FACS. RESULTS: Responders to anti-TNF therapy displayed a significantly higher expression of TNF receptor 2 (TNFR2) but not IL23R on T cells than non-responders prior to anti-TNF therapy. During anti-TNF therapy, there was a significant upregulation of mucosal IL-23p19, IL23R and IL-17A in anti-TNF non-responders but not in responders. Apoptosis-resistant TNFR2+IL23R+ T cells were significantly expanded in anti-TNF non-responders compared with responders, expressed the gut tropic integrins α4β7, and exhibited increased expression of IFN-γ, T-bet, IL-17A and RORγt compared with TNFR2+IL23R- cells, indicating a mixed Th1/Th17-like phenotype. Intestinal TNFR2+IL23R+ T cells were activated by IL-23 derived from CD14+ macrophages, which were significantly more present in non-responders prior to anti-TNF treatment. Administration of IL-23 to anti-TNF-treated mucosal organ cultures led to the expansion of CD4+IL23R+TNFR2+ lymphocytes. Functional studies demonstrated that anti-TNF-induced apoptosis in mucosal T cells is abrogated by IL-23. CONCLUSIONS: Expansion of apoptosis-resistant intestinal TNFR2+IL23R+ T cells is associated with resistance to anti-TNF therapy in Crohn's disease. These findings identify IL-23 as a suitable molecular target in patients with Crohn's disease refractory to anti-TNF therapy.
EVALuna2:34305

High-throughput Raman spectroscopy allows ex vivo characterization of murine small intestinal intra-epithelial lymphocytes (IEL) - Guliev, Rustam R. R.; Vogler, Tina; Arend, Natalie; Eiserloh, Simone; Wiede, Alexander; Kunert, Timo; Dinkel, Martin; Popp, Juergen; Schie, Iwan W. W.; Hildner, Kai; Neugebauer, Ute (Analyst, 2023)
T cells are considered to be critical drivers of intestinal inflammation in mice and people. The so called intra-epithelial lymphocyte (IEL) compartment largely consist of T cells. Interestingly, the specific regulation and contribution of IELs in the context of inflammatory bowel disease remains poorly understood, in part due to the lack of appropriate analysis tools. Powerful, label-free methods could ultimately provide access to this cell population and hence give valuable insight into IEL biology and even more to their disease-related functionalities. Raman spectroscopy has demonstrated over the last few years its potential for reliable cell characterization and differentiation, but its utility in regard to IEL exploration remains unknown. To address this question experimentally, we utilized a murine, T cell-driven experimental model system which is accepted to model human gut inflammation. Here, we repopulated the small intestinal IEL compartment (SI IELs) of Rag1-deficient mice endogenously lacking T cells by transferring naïve CD4+ T helper cells intraperitoneally. Using multivariate statistical analysis, high-throughput Raman spectroscopy managed to define a cell subpopulation ex vivo within the SI IEL pool of mice previously receiving T cells in vivo that displayed characteristic spectral features of lymphocytes. Raman data sets matched flow cytometry analyses with the latter identifying T cell receptor (TCR)αβ+ CD4+ T cell population in SI IELs from T cell-transferred mice, but not from control mice, in an abundance comparable to the one detected by Raman spectroscopy. Hence, in this study, we provide experimental evidence for high-throughput Raman spectroscopy to be a novel, future tool to reliably identify and potentially further characterize the T cell pool of small intestinal IELs ex vivo.
CRIS-Team Scopus Importer:2023-04-20

HLA-DO: a possible switch between GvHD and GvL effect - Zeun, J.; Neubeck, S.; Lang, Vanessa; Flamann, Cindy; Nagel, L.; Kunert, Timo; Vogler, T.; Brey, Stefanie; Hildner, Kai; Bäuerle, Tobias; Büttner-Herold, Maike; Winkler, Thomas; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Hobit- and Blimp-1-driven CD4(+) tissue-resident memory T cells control chronic intestinal inflammation - Zundler, Sebastian; Becker, Emily; Spocinska, Marta; Slawik, Monique; Parga-Vidal, Loreto; Stark, Regina; Wiendl, Maximilian; Atreya, Raja; Rath, Timo; Leppkes, Moritz; Hildner, Kai; Lopez Posadas, Rocío; et al. (Nature Immunology, 2019)
Although tissue-resident memory T cells (T-RM cells) have been shown to regulate host protection in infectious disorders, their function in inflammatory bowel disease (IBD) remains to be investigated. Here we characterized T-RM cells in human IBD and in experimental models of intestinal inflammation. Pro-inflammatory T-RM cells accumulated in the mucosa of patients with IBD, and the presence of CD4(+)CD69(+)CD103(+) T-RM cells was predictive of the development of flares. In vivo, functional impairment of T-RM cells in mice with double knockout of the T-RM-cell-associated transcription factors Hobit and Blimp-1 attenuated disease in several models of colitis, due to impaired cross-talk between the adaptive and innate immune system. Finally, depletion of T-RM cells led to a suppression of colitis activity. Together, our data demonstrate a central role for T-RM cells in the pathogenesis of chronic intestinal inflammation and suggest that these cells could be targets for future therapeutic approaches in IBD.
CRIS-Team WoS Importer:2019-03-06

Human Double-Negative Regulatory T-Cells Induce a Metabolic and Functional Switch in Effector T-Cells by Suppressing mTOR Activity - Haug, Tabea; Aigner, Michael; Peuser, Moritz M.; Strobl, Carolin; Hildner, Kai; Mougiakakos, Dimitrios; Bruns, Heiko; Mackensen, Andreas; Völkl, Simon (Frontiers in Immunology, 2019)
The recently discovered population of TCR alpha b + CD4-/CD8-(double-negative, DN) T-cells are highly potent suppressor cells in mice and humans. In preclinical transplantation models, adoptive transfer of DN T-cells specifically inhibits alloreactive T-cells and prevents transplant rejection or graft-vs.-host disease (GvHD). Interestingly, clinical studies in patients who underwent allogeneic stem cell transplantation reveal an inverse correlation between the frequency of circulating DN T-cells and the severity of GvHD, suggesting a therapeutic potential of human DN T-cells. However, their exact mode of action has not been elucidated yet. Investigating the impact of DN T-cells on conventional T-cells, we found that human DN T-cells selectively inhibit mTOR signaling in CD4 T-cells. Given that mTOR is a critical regulator of cellular metabolism, we further determined the impact of DN T-cells on the metabolic framework of T-cells. Intriguingly, DN T-cells diminished expression of glucose transporters and glucose uptake, whereas fatty acid uptake was not modified, indicating that DN T-cells prevent metabolic adaptation of CD4 T-cells upon activation (i.e., glycolytic switch) thereby contributing to their suppression. Further analyses demonstrated that CD4 T-cells also do not upregulate homing receptors associated with inflammatory processes. In contrast, expression of central memory-cell associated cell surface markers and transcription factors were increased by DN T-cells. Moreover, CD4 T-cells failed to produce inflammatory cytokines after co-culture with DN T-cells, whereas IL-2 secretion was enhanced. Taken together DN T-cells impair metabolic reprogramming of conventional CD4 T-cells by abrogating mTOR signaling, thereby modulating CD4 T-cell functionality. These results uncover a new mechanism of DN T-cell-mediated suppression, pointing out that DN T-cells could serve as cell-based therapy to limit alloreactive immune response.
CRIS-Team WoS Importer:2019-05-03

IL-23 is centrally involved in mediating molecular resistance to anti-TNF therapy in Crohn's disease patients - Schmitt, H.; Billmeier, Ulrike; Dieterich, Walburga; Rath, T.; Sonnewald, Sophia; Reid, Stephen; Hirschmann, S.; Hildner, Kai; Waldner, Maximilian; Mudter, J.; Hartmann, Arndt; Grützmann, Robert; et al. (2018)
EVALuna2:34077

ILC2 Lung-Homing in Cystic Fibrosis Patients: Functional Involvement of CCR6 and Impact on Respiratory Failure - Schulz-Kuhnt, Anja; Greif, Vicky; Hildner, Kai; Knipfer, Lisa; Döbrönti, Michael; Zirlik, Sabine; Fuchs, Florian; Atreya, Raja; Zundler, Sebastian; Lopez Posadas, Rocío; Neufert, Clemens; Ramming, Andreas; et al. (Frontiers in Immunology, 2020)
Cystic fibrosis patients suffer from a progressive, often fatal lung disease, which is based on a complex interplay between chronic infections, locally accumulating immune cells and pulmonary tissue remodeling. Although group-2 innate lymphoid cells (ILC2s) act as crucial initiators of lung inflammation, our understanding of their involvement in the pathogenesis of cystic fibrosis remains incomplete. Here we report a marked decrease of circulating CCR6+ ILC2s in the blood of cystic fibrosis patients, which significantly correlated with high disease severity and advanced pulmonary failure, strongly implicating increased ILC2 homing from the peripheral blood to the chronically inflamed lung tissue in cystic fibrosis patients. On a functional level, the CCR6 ligand CCL20 was identified as potent promoter of lung-directed ILC2 migration upon inflammatory conditions in vitro and in vivo using a new humanized mouse model with light-sheet fluorescence microscopic visualization of lung-accumulated human ILC2s. In the lung, blood-derived human ILC2s were able to augment local eosinophil and neutrophil accumulation and induced a marked upregulation of pulmonary type-VI collagen expression. Studies in primary human lung fibroblasts additionally revealed ILC2-derived IL-4 and IL-13 as important mediators of this type-VI collagen-inducing effect. Taken together, the here acquired results suggest that pathologically increased CCL20 levels in cystic fibrosis airways induce CCR6-mediated lung homing of circulating human ILC2s. Subsequent ILC2 activation then triggers local production of type-VI collagen and might thereby drive extracellular matrix remodeling potentially influencing pulmonary tissue destruction in cystic fibrosis patients. Thus, modulating the lung homing capacity of circulating ILC2s and their local effector functions opens new therapeutic avenues for cystic fibrosis treatment.
CRIS-Team Scopus Importer:2020-06-02
Keywords: CCR6; cystic fibrosis; group-2 innate lymphoid cells; tissue remodeling; type-VI collagen

Immunopathogenesis of IBD: Batf as a Key Driver of Disease Activity - Hildner, Kai; Punkenburg, Elise; Abendroth, Benjamin; Neurath, Markus (Digestive Diseases, 2016)
Inflammatory bowel diseases (IBDs) represent a group of chronic immune-mediated disorders that are influenced by a genetic predisposition and additional environmental triggers. Genome-wide association studies strongly implicate that a number of immune system-related genetic variations are critically contributing to the initiation and promotion of intestinal inflammation. Especially the identification of the strong association of a series of single nucleotide polymorphisms including interleukin (IL)-23R, CCR6, signal transducer and activator of transcription 3 (Stat3) and Stat4 with IBD susceptibility point at a critical involvement of T cells and especially of IL-17a-producing Th17 cells in the immune pathogenesis of IBD. In line with this hypothesis, a series of preclinical studies have unequivocally established that T cells are key drivers of immune-mediated colitis. Interestingly, especially Th17 cells were identified to be highly prevalent in inflamed IBD tissues, a finding that seems to be functionally relevant as genetic inactivation studies in the mouse resulted in almost complete suppression of colitis development.While targeting Th17 cell differentiation regulating transcription factors, as retinoic acid-related orphan receptor gamma t (ROR?t) is effective in preventing murine colitis, one concern of drugs targeting ROR?t in a clinical setting represents the large body of murine data unambiguously demonstrating that additional pathways within and outside the immune system are equally ROR?t-dependent increasing the risk of undesirable side effects. The AP1 transcription factor Batf (B cell-activating transcription factor) appears to exclusively regulate pathways within lymphocytes. Importantly, Batf represents a central regulator of Th17 cell development and is strongly upregulated within IBD-affected tissues. Employing 2 acute colitis models, we demonstrate in this study that Batf-expressing T cells are critical drivers of T cell-mediated colitis while in contrast to Stat3 loss of Batf does not affect intestinal epithelial cell homeostasis ex vivo.Targeting Batf in IBD emerges as an attractive therapeutic approach disabling colitogenic T cell activities while sparing off-target effects in the intestinal epithelial cell compartment.
EVALuna2:2187

Induction of Intestinal Graft-versus-host Disease and Its Mini-endoscopic Assessment in Live Mice - Buchele, Vera; Büttner-Herold, Maike; Vogler, Tina; Neurath, Markus; Hildner, Kai (Journal of Visualized Experiments, 2019)
Acute graft-versus-host disease (GvHD) represents the most severe complication that patients previously undergoing allogeneic hematopoietic stem cell transplantation (allo-HCT) face and is frequently associated with a poor clinical outcome. While, for instance, GvHD manifestations of the skin are usually responsive to established immune-suppressive therapies and are, hence, not taking a fatal course, the presence and the intensity of intestinal GvHD, especially of the mid-to-lower parts of the gut, strongly influence the outcome and overall survival of patients with acute GvHD. Therapeutic options are essentially limited to the classic immune-suppressive agents yielding only moderate disease-mitigating effects. Hence, detailed knowledge about the tissue-resident immune cascade, changes in the intestinal microbiota, and the stromal response prior, upon, and after intestinal GvHD onset are urgently needed to understand the events and mechanisms underlying its pathogenesis and to develop innovative therapeutic options. Murine models of GvHD are frequently employed to identify and functionally assess molecules and pathways putatively driving intestinal GvHD. However, means to specifically monitor and evaluate intestinal inflammation over time are essentially lacking since established scores to assess and grade acute GvHD are routinely comprised of various parameters which rather reflect systemic GvHD manifestations. The detailed evaluation of intestinal GvHD has been restricted to studies using euthanized mice, thereby essentially excluding longitudinal (i.e., kinetic) analyses of the colonic compartment under a given experimental condition (e.g., antibody-mediated blockade of a proinflammatory cytokine) in live mice (i.e., in vivo). The mini-endoscopic in situ assessment of the distal colon of alloHCT-treated mice described here allows a) a detailed macroscopic evaluation of different aspects of intestinal inflammation and b) the option to collect tissue samples for downstream analyses at various time points over the course of the observation period. Overall, the mini-endoscopic approach provides a major advance in preclinical noninvasive monitoring and assessment of intestinal GvHD.
CRIS-Team WoS Importer:2019-04-12

Interleukin-3 is a predictive marker for severity and outcome during SARS-CoV-2 infections - Bénard, Alan; Jacobsen, Anne; Brunner, Maximilian; Krautz, Christian; Klösch, Bettina; Swierzy, Izabela; Naschberger, Elisabeth; Podolska, Malgorzata; Kouhestani, Dina; David, Paul; Birkholz, Torsten; Castellanos, Ixchel; et al. (Nature Communications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide health threat. In a prospective multicentric study, we identify IL-3 as an independent prognostic marker for the outcome during SARS-CoV-2 infections. Specifically, low plasma IL-3 levels is associated with increased severity, viral load, and mortality during SARS-CoV-2 infections. Patients with severe COVID-19 exhibit also reduced circulating plasmacytoid dendritic cells (pDCs) and low plasma IFNα and IFNλ levels when compared to non-severe COVID-19 patients. In a mouse model of pulmonary HSV-1 infection, treatment with recombinant IL-3 reduces viral load and mortality. Mechanistically, IL-3 increases innate antiviral immunity by promoting the recruitment of circulating pDCs into the airways by stimulating CXCL12 secretion from pulmonary CD123+ epithelial cells, both, in mice and in COVID-19 negative patients exhibiting pulmonary diseases. This study identifies IL-3 as a predictive disease marker for SARS-CoV-2 infections and as a potential therapeutic target for pulmunory viral infections.
CRIS-Team Scopus Importer:2021-03-05

Intestinal graft-versus-host disease is driven by BATF-dependent IL-7R(hi)GM-CSF+ T cells - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Buettner-Herold, Maike; Kitowski, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (2018)
EVALuna2:207769

Label-Free Characterization and Quantification of Mucosal Inflammation in Common Murine Colitis Models With Multiphoton Imaging - Kreiß, Lucas; Thoma, Oana-Maria; Lemire, Sarah; Lechner, Kristina; Carlé, Birgitta-Elisabeth; Dilipkumar, Ashwathama; Kunert, Timo; Scheibe, Kristina; Heichler, Christina; Merten, Anna-Lena; Weigmann, Benno; Neufert, Clemens; et al. (Inflammatory Bowel Diseases, 2022)
Background Clinical challenges in inflammatory bowel diseases require microscopic in vivo evaluation of inflammation. Here, label-free imaging holds great potential, and recently, our group demonstrated the advantage of using in vivo multiphoton endomicroscopy for longitudinal animal studies. This article extends our previous work by in-depth analysis of label-free tissue features in common colitis models quantified by the multiphoton colitis score (MCS). Methods Fresh mucosal tissues were evaluated from acute and chronic dextran sulfate sodium (DSS), TNBS, oxazolone, and transfer colitis. Label-free imaging was performed by using second harmonic generation and natural autofluorescence. Morphological changes in mucosal crypts, collagen fibers, and cellularity in the stroma were analyzed and graded. Results Our approach discriminated between healthy (mean MCS = 2.5) and inflamed tissue (mean MCS > 5) in all models, and the MCS was validated by hematoxylin and eosin scoring of the same samples (85.2% agreement). Moreover, specific characteristics of each phenotype were identified. While TNBS, oxazolone, and transfer colitis showed high cellularity in stroma, epithelial damage seemed specific for chronic, acute DSS and transfer colitis. Crypt deformations were mostly observed in acute DSS. Conclusions Quantification of label-free imaging is promising for in vivo endoscopy. In the future, this could be valuable for monitoring of inflammatory pathways in murine models, which is highly relevant for the development of new inflammatory bowel disease therapeutics.
CRIS-Team WoS Importer:2022-10-07

Label-Free In Vivo Histopathology of Experimental Colitis via 3-Channel Multiphoton Endomicroscopy - Kreiß, Lucas; Thoma, Oana Maria; Dilipkumar, Ashwathama; Carlé, Birgitta-Elisabeth; Longequeue, Pascal; Kunert, Timo; Rath, Timo; Hildner, Kai; Neufert, Clemens; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; et al. (Gastroenterology, 2020)
CRIS-Team Scopus Importer:2020-08-28

Novel T cell/organoid culture system allows ex vivo modeling of intestinal graft-versus-host disease - Matthe, Diana; Dinkel, Martin; Schmid, Benjamin; Vogler, Tina; Neurath, Markus; Poeck, Hendrik; Neufert, Clemens; Büttner-Herold, Maike; Hildner, Kai (Frontiers in Immunology, 2023)
Acute graft-versus-host disease (GvHD) remains the biggest clinical challenge and prognosis-determining complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Donor T cells are acceptedly key mediators of alloreactivity against host tissues and here especially the gut. In support of previous studies, we found that the intestinal intra-epithelial lymphocyte (IEL) compartment was dynamically regulated in the course of MHC class I full mismatch allo-HSCT. However, while intestinal epithelial cell (IEC) damage endangers the integrity of the intestinal barrier and is a core signature of intestinal GvHD, the question whether and to what degree IELs are contributing to IEC dysregulation is poorly understood. To study lymphoepithelial interaction, we employed a novel ex vivo T cell/organoid co-culture model system. Here, allogeneic intra-epithelial T cells were superior in inducing IEC death compared to syngeneic IEL and allogeneic non-IEL T cells. The ability to induce IEC death was predominately confined to TCRβ+ T cells and was executed in a largely IFNγ-dependent manner. Alloreactivity required a diverse T cell receptor (TCR) repertoire since IELs genetically modified to express a TCR restricted to a single, non-endogenous antigen failed to mediate IEC pathology. Interestingly, minor histocompatibility antigen (miHA) mismatch was sufficient to elicit IEL-driven IEC damage. Finally, advanced live cell imaging analyses uncovered that alloreactive IELs patrolled smaller areas within intestinal organoids compared to syngeneic controls, indicating their unique migratory properties within allogeneic IECs. Together, we provide here experimental evidence for the utility of a co-culture system to model the cellular and molecular characteristics of the crosstalk between IELs and IEC in an allogeneic setting ex vivo. In the light of the emerging concept of dysregulated immune-epithelial homeostasis as a core aspect of intestinal GvHD, this approach represents a novel experimental system to e.g. screen therapeutic strategies for their potential to normalize T cell/IEC- interaction. Hence, analyses in pre-clinical in vivo allo-HSCT model systems may be restricted to hereby positively selected, promising approaches.
CRIS-Team Scopus Importer:2023-09-22
Keywords: allogeneic hematopoietic stem cell transplantation; alloreactive T cell; epithelial cell death; ex vivo model; graft-versus-host disease; GvHD; intestinal organoids; intraepithelial lymphocytes

Nr4a1-dependent non-classical monocytes are important for macrophage-mediated wound healing in the large intestine - Heidbreder, Karin; Sommer, Katrin; Wiendl, Maximilian; Müller, Tanja; Atreya, Imke; Hildner, Kai; Neurath, Markus; Zundler, Sebastian (Frontiers in Immunology, 2023)
Introduction: Macrophages play an important role in intestinal wound healing. However, the trajectories from circulating monocytes to gut macrophages are incompletely understood. Methods: Taking advantage of mice depleted for non-classical monocytes due to deficiency for the transcription factor Nr4a1, we addressed the relevance of non-classical monocytes for large intestinal wound healing using flow cytometry, in vivo wound healing assays and immunofluorescence. Results: We show that wound healing in Nr4a1-deficient mice is substantially delayed and associated with reduced peri-lesional presence of macrophages with a wound healing phenotype. Discussion: Our data suggest that non-classical monocytes are biased towards wound healing macrophages. These insights might help to understand, how targeting monocyte recruitment to the intestine can be used to modulate intestinal macrophage functions.
CRIS-Team Scopus Importer:2023-02-10
Keywords: gut homing; intestinal wound healing; macrophages; monocytes; Nr4a1 (Nur77)

Protection of Batf3-deficient mice from experimental cerebral malaria correlates with impaired cytotoxic T-cell responses and immune regulation - Kuehlwein, Janina M.; Borsche, Max; Korir, Patricia J.; Risch, Frederic; Mueller, Ann-Kristin; Huebner, Marc P.; Hildner, Kai; Hoerauf, Achim; Dunay, Ildiko Rita; Schumak, Beatrix (Immunology, 2019)
Excessive inflammatory immune responses during infections with Plasmodium parasites are responsible for severe complications such as cerebral malaria (CM) that can be studied experimentally in mice. Dendritic cells (DCs) activate cytotoxic CD8+ T-cells and initiate immune responses against the parasites. Batf3−/− mice lack a DC subset, which efficiently induces strong CD8 T-cell responses by cross-presentation of exogenous antigens. Here we show that Batf3−/− mice infected with Plasmodium berghei ANKA (PbA) were protected from experimental CM (ECM), characterized by a stable blood−brain barrier (BBB) and significantly less infiltrated peripheral immune cells in the brain. Importantly, the absence of ECM in Batf3−/− mice correlated with attenuated responses of cytotoxic T-cells, as their parasite-specific lytic activity as well as the production of interferon gamma and granzyme B were significantly decreased. Remarkably, spleens of ECM-protected Batf3−/− mice had elevated levels of regulatory immune cells and interleukin 10. Thus, protection from ECM in PbA-infected Batf3−/− mice was associated with the absence of strong CD8+ T-cell activity and induction of immunoregulatory mediators and cells.
CRIS-Team Scopus Importer:2019-11-26
Keywords: dendritic cells; experimental cerebral malaria; inflammation; Plasmodium; T-cells

Public spirometry for primary prevention of COPD - Zirlik, Sabine; Wich, Christina; Frieser, Markus; Hildner, Kai; Kleye, Christin; Neurath, Markus; Fuchs, Florian S. (Journal of Evaluation in Clinical Practice, 2014)
The most effective action for primary prevention of chronic obstructive lung disease is smoking cessation early enough. In secondary prevention, smokers with airway obstruction were more likely to quit smoking. The aim of this study was to evaluate the impact of a public spirometry on smoking habits in terms of primary prevention.Spirometry with its medical analysis was offered to visitors of a local public event called 'Lange Nacht der Wissenschaften' ('Long night of sciences'). The impact of results on smoking habits was evaluated in all smokers with an anonymized questionnaire afterwards.Two hundred fifty-seven people with the median age of 30 years (interquartile range 22-46) were examined. Out of 44 current smokers (17.1%), only two individuals showed a prebronchodilator FEV1/forced vital capacity-value <0.7. Fourteen smokers stated to have an increased motivation to quit smoking whereas 28 smokers declared that their motivation to quit smoking was independent of spirometry result. These smokers were significantly younger (median age 28 vs. 40 years, P = 0.025) without differences in spirometry results or smoking habits.In an unselected population with a high amount of younger adults, normal spirometry did not show a short-term benefit for primary prevention of chronic obstructive lung disease in terms of increasing motivation to quit smoking.
EVALuna2:1869

Resolution of acute intestinal graft-versus-host disease - Thiagarajan, Sindhu; Neurath, Markus; Hildner, Kai (Seminars in Immunopathology, 2019)
Allogeneic transplantation of hematopoietic stem cells (allo-HCT) represents an increasingly employed therapeutic approach to potentially cure patients suffering from life-threatening malignant and autoimmune disorders. Despite its lifesaving potential, immune-mediated allo-reactivity inherent to the allogeneic transplantation can be observed within up to 50% of all allo-HCT patients regularly resulting in the manifestation of acute and/or chronic graft-versus-host disease (GvHD). Mechanistically, especially donor T cells are assumed to chiefly drive inflammation that can occur in virtually all organs, with the skin, liver, and gut representing as the most frequently affected anatomic sites. Especially in the presence of intestinal manifestations of GvHD, the risk that the disease takes a life-threatening, potentially fatal course is significantly increased. In the light of a rapid gain of knowledge in respect to decode innate and adaptive immunity related mechanisms as, e.g., cytokine networks, intracellular signaling pathways or environmental triggers as, e.g., the intestinal microbiota and the development of novel therapeutic approaches, detailed insight into endogenous mechanisms seeking to counterbalance the proinflammatory machinery or to proactively foster signals promoting the resolution of allo-driven intestinal inflammation is emerging. Here, we seek to highlight the key aspects of those mechanisms involved in and contributing to the resolution of GvHD-associated intestinal inflammation. Concomitantly, we would like to briefly outline and discuss promising future experimental targets suitable to be therapeutically employed to directionally deflect the tissue response from a proinflammatory to an inflammation-resolving type of intestinal GvHD after allo-HCT.
CRIS-Team WoS Importer:2019-11-15

Round-Robin test for the histological diagnosis of acute colonic Graft-versus-Host disease validating established histological criteria and grading systems - Hippe, Katrin; Kreft, Andreas; Reu-Hofer, Simone; Rosenwald, Andreas; Ferrazzi, Fulvia; Daniel, Christoph; Amann, Kerstin Ute; Kraus, Sabrina; Holler, Ernst; Kandulski, Arne; Hirsch, Daniela; Buttner, Anke; et al. (Virchows Archiv, 2023)
Histomorpholgy is one of the mainstays of acute Graft-versus-host disease (GvHD) diagnosis. However, concerns about reproducibility and the most appropriate grading system question its usefulness. Our aim was to assess histomorphological parameters and previously reported grading systems for GvHD regarding reproducibility and validity. Moreover, we propose that sum scores, derived by combining separately scored morphological parameters into a total score, might provide a simplified but equally effective means to grade GvHD. A total of 123 colon biopsies were assessed across four pathologists for intestinal GvHD using a Round-Robin test and results were correlated with clinical findings. Interobserver reproducibility was high for histological parameters that were evaluated as indicators of acute GvHD. Published grading systems were moderately reproducible (ICC 0.679–0.769) while simplified sum scores, in comparison, showed better interrater reliability (ICC 0.818–0.896). All grading systems and sum scores were associated with clinical signs of GvHD and in part with therapy response and survival. However, they were not able to stratify patients according to the clinical severity of GvHD. In a hot-spot analysis 1 crypt apoptotic body (CAB) in 10 crypts was a reasonable cut-off value for minimal diagnostic criteria of GvHD. In conclusion, histology can contribute to the diagnosis of GvHD and is reproducible. Published grading systems are able to reflect clinical findings as are simplified sum scores, which showed improved reproducibility and might be easier to handle as they are based on adding up histological parameters rather than transferring histological findings into a separate grading system. Sum scores will have to be further tested in a prospective setting.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Acute Graft-versus-host disease; Colon biopsy; Grading; Interobserver agreement; Round-Robin test

Spatial Single Cell Profiling Using Imaging Mass Cytometry: Inflammatory Versus Penetrating Crohn's Disease - Lehmann, Malte; Weixler, Benjamin; Elezkurtaj, Sefer; Loddenkemper, Christopher; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Fistula formation is a major complication in Crohn's disease [CD] and the role of the immune cell compartment remains to be elucidated. Thus, we compared the immune cell compartment of CD fistula to inflammatory CD colitis using imaging mass cytometry [IMC] and immunofluorescence. Methods: A 36-marker panel including structural, functional, and lineage markers for use in IMC was established. This panel was applied to analyse paraffin-embedded CD fistula tract [n = 11], CD colitis [n = 10], and colon samples from non-inflamed controls [n = 12]. Computational methods for cell segmentation, dimensionality reduction, and cell type clustering were used to define cell populations for cell frequency, marker distribution, and spatial neighbourhood analysis. Multiplex immunofluorescence was used for higher resolution spatial analysis. Results: Analysis of cell frequencies in CD fistulas compared to CD colitis and control colonic samples revealed a significant increase in neutrophils, effector cytotoxic T cells, and inflammatory macrophages in CD fistula samples, whereas regulatory T cells were decreased. Neutrophils in CD fistula expressed significantly more matrix metalloproteinase 9 [MMP9], correlating with extracellular matrix remodelling. Neighbourhood analysis revealed a strong association between MMP9+ neutrophils and effector cytotoxic T cells in both CD fistulas and colitis. Conclusions: This study presents the first highly multiplexed single cell analysis of the immune cell compartment of CD fistulas and their spatial context. It links immune cell dynamics, particularly MMP9+ neutrophils, to extracellular matrix remodelling in CD fistulas, offering insights into the complex network of cellular interactions and potential therapeutic targets for CD complications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: fistula; imaging mass cytometry; Penetrating Crohn's disease

STAT3 Activation in Th17 and Th22 Cells Controls IL-22-Mediated Epithelial Host Defense during Infectious Colitis - Backert, Ingo; Koralov, Sergei B.; Wirtz, Stefan; Kitowski, Vera; Billmeier, Ulrike; Martini, Eva; Hofmann, Katharina; Hildner, Kai; Wittkopf, Nadine; Brecht, Katrin; Waldner, Maximilian; Rajewsky, Klaus; et al. (Journal of Immunology, 2014)
The Citrobacter rodentium model mimics the pathogenesis of infectious colitis and requires sequential contributions from different immune cell populations, including innate lymphoid cells (ILCs) and CD4(+) lymphocytes. In this study, we addressed the role of STAT3 activation in CD4(+) cells during host defense in mice against C. rodentium. In mice with defective STAT3 in CD4(+) cells (Stat3(?CD4)), the course of infection was unchanged during the innate lymphoid cell-dependent early phase, but significantly altered during the lymphocyte-dependent later phase. Stat3(?CD4) mice exhibited intestinal epithelial barrier defects, including downregulation of antimicrobial peptides, increased systemic distribution of bacteria, and prolonged reduction in the overall burden of C. rodentium infection. Immunomonitoring of lamina propria cells revealed loss of virtually all IL-22-producing CD4(+) lymphocytes, suggesting that STAT3 activation was required for IL-22 production not only in Th17 cells, but also in Th22 cells. Notably, the defective host defense against C. rodentium in Stat3(?CD4) mice could be fully restored by specific overexpression of IL-22 through a minicircle vector-based technology. Moreover, expression of a constitutive active STAT3 in CD4(+) cells shaped strong intestinal epithelial barrier function in vitro and in vivo through IL-22, and it promoted protection from enteropathogenic bacteria. Thus, our work indicates a critical role of STAT3 activation in Th17 and Th22 cells for control of the IL-22-mediated host defense, and strategies expanding STAT3-activated CD4(+) lymphocytes may be considered as future therapeutic options for improving intestinal barrier function in infectious coliti
EVALuna2:1843

Targeting Inflammatory T Helper Cells via Retinoic Acid-Related Orphan Receptor Gamma t Is Ineffective to Prevent Allo-Response-Driven Colitis - Buchele, Vera; Abendroth, Benjamin; Buettner-Herold, Maike; Vogler, Tina; Rothamer, Johanna; Ghimire, Sakhila; Ullrich, Evelyn; Holler, Ernst; Neurath, Markus; Hildner, Kai (Frontiers in Immunology, 2018)
Intestinal graft-versus-host disease (GvHD) is a life-threatening, inflammatory donor T cell-mediated complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). In the light of the reported efficacy of interleukin-23 (IL-23)-blockade to mitigate syngeneic intestinal inflammation in inflammatory bowel disease patients, targeting IL-23 and thereby interleukin-17a (IL-17a) producing T helper (Th17) cells as the T cell subset assumed to be mostly regulated by IL-23, has emerged as a putatively general concept to harness immune-mediated mucosal inflammation irrespective of the underlying trigger. However, the role of Th17 cells during allo-response driven colitis remains ambiguous due to a series of studies with inconclusive results. Interestingly, we recently identified granulocyte-macrophage colony-stimulating factor (GM-CSF+) T cells to be promoted by interleukin-7 (IL-7) signaling and controlled by the activating protein-1 transcription factor family member basic leucine zipper transcription factor ATF-like (BATF) as critical mediators of intestinal GvHD in mice. Given the dual role of BATF, the contribution of IL-23-mediated signaling within donor T cells and bona fide Th17 cells remains to be delineated from the regulation of GM-CSF+ T cells in the absence of BATF. Here, we found in a complete MHC class I-mismatched model that genetic inactivation of the IL-23 receptor (IL-23R) or the transcription factor retinoic acid-related orphan receptor gamma t (RORγt) within donor T cells similarly ablated Th17 cell formation in vivo but preserved the T cells' ability to induce intestinal GvHD in a compared to wild-type controls indistinguishable manner. Importantly, RORγt-independent manifestation of intestinal GvHD was completely dependent on BATF-regulated GM-CSF+ T cells as BATF/RORγt double-deficient T cells failed to induce colitis and the antibody-mediated blockage of IL-7/IL-7R interaction and GM-CSF significantly diminished signs of intestinal GvHD elicited by RORγt-deficient donor T cells. Finally, in analogy to our murine studies, colonic RORC expression levels inversely correlated with the presence of GvHD in allo-HSCT patients. Together, this study provides a crucial example of a BATF-dependent, however, IL-23R signaling- and RORγt-, i.e., Th17 fate-independent regulation of a colitogenic T cell population critically impacting the current understanding of intestinal GvHD.
EVALuna2:34273

Th17 Cell-Mediated Colitis Is Positively Regulated by Interferon Regulatory Factor 4 in a T Cell-Extrinsic Manner - Buchele, Vera; Konein, Patrick; Vogler, Tina; Kunert, Timo; Enderle, Karin; Khan, Hanif; Büttner-Herold, Maike; Lehmann, Christian; Amon, Lukas; Wirtz, Stefan; Dudziak, Diana; Neurath, Markus; et al. (Frontiers in Immunology, 2021)
Inflammatory bowel diseases (IBDs) are characterized by chronic, inflammatory gastrointestinal lesions and often require life-long treatment with immunosuppressants and repetitive surgical interventions. Despite progress in respect to the characterization of molecular mechanisms e.g. exerted by TNF-alpha, currently clinically approved therapeutics fail to provide long-term disease control for most patients. The transcription factor interferon regulatory factor 4 (IRF4) has been shown to play important developmental as well as functional roles within multiple immune cells. In the context of colitis, a T cell-intrinsic role of IRF4 in driving immune-mediated gut pathology is established. Here, we conversely addressed the impact of IRF4 inactivation in non-T cells on T cell driven colitis in vivo. Employing the CD4+CD25− naïve T cell transfer model, we found that T cells fail to elicit colitis in IRF4-deficient compared to IRF4-proficient Rag1−/− mice. Reduced colitis activity in the absence of IRF4 was accompanied by hampered T cell expansion both within the mesenteric lymph node (MLN) and colonic lamina propria (cLP). Furthermore, the influx of various myeloids, presumably inflammation-promoting cells was abrogated overall leading to a less disrupted intestinal barrier. Mechanistically, gene profiling experiments revealed a Th17 response dominated molecular expression signature in colon tissues of IRF4-proficient, colitic Rag1−/− but not in colitis-protected Rag1−/−Irf4−/− mice. Colitis mitigation in Rag1−/−Irf4−/− T cell recipients resulted in reduced frequencies and absolute numbers of IL-17a-producing T cell subsets in MLN and cLP possibly due to a regulation of conventional dendritic cell subset 2 (cDC2) known to impact Th17 differentiation. Together, extending the T cell-intrinsic role for IRF4 in the context of Th17 cell driven colitis, the provided data demonstrate a Th17-inducing and thereby colitis-promoting role of IRF4 through a T cell-extrinsic mechanism highlighting IRF4 as a putative molecular master switch among transcriptional regulators driving immune-mediated intestinal inflammation through both T cell-intrinsic and T cell-extrinsic mechanisms. Future studies need to further dissect IRF4 controlled pathways within distinct IRF4-expressing myeloid cell types, especially cDC2s, to elucidate the precise mechanisms accounting for hampered Th17 formation and, according to our data, the predominant mechanism of colitis protection in Rag1−/−Irf4−/− T cell receiving mice.
CRIS-Team Scopus Importer:2021-02-26
Keywords: inflammatory bowel disease (IBD); interferon regulatory factor 4 (IRF4); intestinal inflammation; myeloid cells; Th17

The activating protein 1 transcription factor basic leucine zipper transcription factor, ATF-like (BATF), regulates lymphocyte- and mast cell-driven immune responses in the setting of allergic asthma - Ubel, Caroline; Sopel, Nina; Graser, Anna; Hildner, Kai; Reinhardt, Cornelia; Zimmermann, Theodor; Rieker, Ralf Joachim; Maier, Anja; Neurath, Markus; Murphy, Kenneth M.; Finotto, Susetta (Journal of Allergy and Clinical Immunology, 2014)
Mice without the basic leucine zipper transcription factor, ATF-like (BATF) gene (Batf(-/-)) lack TH17 and follicular helper T cells, which demonstrates that Batf is a transcription factor important for T- and B-cell differentiation.In this study we examined whether BATF expression would influence allergic asthma.In a cohort of preschool control children and children with asthma, we analyzed BATF mRNA expression using real-time PCR in PBMCs. In a murine model of allergic asthma, we analyzed differences in this allergic disease between wild-type, Batf transgenic, and Batf(-/-) mice.In the absence of corticosteroid treatment, children with recurrent asthma have a significant increase in BATF mRNA expression in their PBMCs. Batf(-/-) mice display a significant reduction in the pathophysiologic responses seen in asthmatic wild-type littermates. Moreover, we discovered a decrease in IL-3 production and IL-3-dependent mast cell development in Batf(-/-) mice. By contrast, IFN-? was induced in lung CD4(+) and CD8(+) T cells. Intranasal delivery of anti-IFN-? antibodies induced airway hyperresponsiveness and inflammation in wild-type but not in Batf(-/-) mice. Transgenic overexpression of Batf under the control of the CD2 promoter/enhancer augmented lung inflammation and IgE levels in the setting of experimental asthma.BATF is increased in non-steroid-treated asthmatic children. Targeting BATF expression resulted in amelioration of the pathophysiologic responses seen in children with allergic asthma, and BATF has emerged as a novel target for antiasthma interventions.
EVALuna2:1742